(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To map the social determinants of health related to diabetic foot ulcers. Method: Scoping review, as established by the Joanna Briggs Institute, registered on the Open Science Framework platform. Data were gathered from fourteen databases without time or language restrictions. Selection criteria included studies that met the search strategy: adults of both genders, social determinants of health related to diabetic foot ulcers, as defined by the World Health Organization, in hospital, outpatient, and home care settings. The World Health Organization model of social determinants of health model was used. Results: A total of 1,371 studies were identified, of which 80 were included in the final sample. The primary determinants identified were structural factors such as culture and social values (3); gender (12); and intermediary factors, including biological factors (18) and behavioral factors (13); social capital and social cohesion (3) were also highlighted, with most studies published in English in 2021. Conclusion: Among the structural determinants, culture, social values, and gender were predominant, while biological factors were the leading intermediary determinants. Social capital shows an emerging area to identify the role of family, community, and health institutions in the care of diabetic foot ulcer.